Development of an Alumni Data Processing Information System Using the SDLC Modeling System Development Method - Mahardika Inra Takaendengan; Eric Alfonsius; Wisard Widsly Kalengkongan (Jurnal Ilmiah Sistem Informasi Akuntansi, 2023)
The development of information systems for processing alumni data is the process of creating an information system that can process existing alumni data within the scope of the school. The object of research in this study took place at SMA Negeri I Dampelas. The purpose of this research is to design and build an information system that can process alumni data. This can make it easier for research sites in terms of recording alumni data, be it a study tracer, and providing news related to existing alumni so that alumni can contribute to the school. The results of this study resulted in the design and development of a system that meets the need to process alumni data and works as it should, and the results of the effectiveness of the system have been tested using qualitative testing with a Likert scale measurement showing a result of 85.47% with a very feasible category. so that it can be the basis for implementing the website.